PENGARUH LABA, ARUS KAS OPERASI DAN ARUS KAS BEBAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN NON-KEUANGAN (TAHUN 2008-2017) - Fadhil Dhaneswara; Haryanto Haryanto (Diponegoro Journal of Accounting, 2019)
This research was conducted to analyze the effect of Earnings, Operating Cash Flow and Free Cash Flows on Dividend Policy on Non-Financial Companies. This research refers to research conducted by Kighir, Omar and Mohamed (2015).The population of this study are all non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2008-2017. Total observations amounted to 410 determined by purposive sampling method. This study uses the OLS method to test hypotheses. The results of the study show that the earnings and operating cash flow variables have a significant positive effect on dividend policy. However, the free cash flow variable has no significant effect on dividend policy.